EVALUATION OF FOOTBALL DEVELOPMENT PROGRAM AT ASIOP FOOTBALL ACADEMY IN JAKARTA - Fitriani; Firmansyah Dlis; Aan Wasan (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to evaluate the context component (program background, vision, and mission, objectives, strategies, organizational structure), and training development programs and management programs, evaluate the Input component (systems for recruiting and coaching trainers, facility support, student recruitment and coaching systems, training program, parental support and views, financial support, and enforcement of rules). To evaluate the components of the process implementation, monitoring and evaluation of the program. To evaluate the components of the product (individual and team results and contributions to Indonesian football). This study uses a qualitative method. The subjects in this study were the overall components of ASIOP Football Academy, namely administrators, coaches, students and parents. Data collection techniques used are observation, interviews, documents, and data triangulation. The data analysis techniques used are as follows: (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing and verification. This study resulted in (1) Context evaluation of soccer coaching at ASIOP Football Academy being in a good category, (2) Evaluation of Input on soccer coaching at ASIOP Football Academy being in a good category, (3) Evaluation of soccer coaching process at ASIOP Football Academy. ASIOP Football Academy is in a good category, (4) Product evaluation of football coaching at ASIOP Football Academy is in a good category.